Outcome of NEXGEN® fixed bearing and posterior stabilising total knee replacement - Noor Rahin, Mohd Shahidan; Siron, Khairul Nizam; Japar Khan, Ed Simor Khan Mor; Zulkifly, Ahmad Hafiz; Harris, Mohammed (IIUM Medical Journal Malaysia, 2016)
Introduction: Total knee arthroplasty (TKA) represents a major advance in the treatment of degenerative joint disease, providing excellent restoration of joint function and pain relief. This study aim to evaluate the survival analysis of the implant, the functional and knee scores outcome and to identify a complication following Nexgen fixed bearing and posterior stabilizing total knee replacement. Methods: The present study was conducted to retrospectively review the results of all primary TKA performed at Hospital Tengku Ampuan Afzan over a period of 15 years from 2000 to 2015. The study sample consisted of 160 TKA. Oxford knee score and SF 36 were used and statistical analysis of both knee scores and functional scores were compared using SPSS software. Survivorship analysis was compared using the Kaplan-Meier method. Endpoints of implant defined as revision with removal of implant and addition or exchange of prosthetic components. Results: Functional and knee score post operatively was excellent and good. Mean range of movement of knee during the study period were left 107.50 degrees and right 106.49 degrees. Mean femoral flexion angle is 92.38 degrees and mean tibial angle is 89.48 degrees. The outcome categories for the Oxford knee score have 101 patients showed excellent result, 41 patients good, and 18 patients fair. In this study mean total SF 36 score is 80.99. Conclusions: The outcome shows that total knee replacement is a reproducible surgery for which a trained surgeon will be able to produce excellent and good results.